2021
DOI: 10.5194/bg-2021-70
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methane in Zackenberg Valley, NE Greenland: Multidecadal growing season fluxes of a high Arctic tundra

Abstract: Abstract. The carbon balance of high-latitude terrestrial ecosystems plays an essential role in the atmospheric concentration of trace gases, including carbon dioxide (CO2) and methane (CH4). Increasing levels of atmospheric methane have contributed to ~20 % of the observed global warming since the pre-industrial era. Rising temperatures in the Arctic are expected to promote the release of methane from Arctic ecosystems. Still, existing methane flux data collection efforts are sparse and highly scattered, and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The large taxonomic shifts in the rRNA pool suggest that the ancient carbon that became available due to warmer temperatures at these depths allows decomposers to thrive. Former studies have shown that methane emissions from this site were variable in both space and time during collapse (Scheller et al, 2021), which highlights the potential of a biogenic carbon release.…”
Section: Discussionmentioning
confidence: 97%
“…The large taxonomic shifts in the rRNA pool suggest that the ancient carbon that became available due to warmer temperatures at these depths allows decomposers to thrive. Former studies have shown that methane emissions from this site were variable in both space and time during collapse (Scheller et al, 2021), which highlights the potential of a biogenic carbon release.…”
Section: Discussionmentioning
confidence: 97%